Socialization of Financial Literacy and Safe Investment in the Banjarejo Village Community, Madiun City - Herawati, Novy Rachma; Faujianto, Samsu Anhari; Bakti, Nurimansyah Setivia (Journal of Community Practice and Social Welfare, 2025)
The Socialization of Financial Literacy and Safe Investment in the Banjarejo Village Community of Madiun City aims to provide a deeper understanding to the Banjarejo Village community of Madiun City, especially vulnerable groups such as MSMEs, housewives, and the younger generation about the importance of managing finances wisely and investing safely. This program also provides education on choosing financial products that are legal and supervised by relevant authorities, such as the Financial Services Authority (OJK). This socialization activity is part of the community service activities in the Banjarejo Village of Madiun City. Implementation by conducting an initial survey and interviews with the local community to identify their level of financial literacy, their needs related to financial education, and common investment patterns. The activity was carried out in the Banjarejo Village of Madiun City on January 19, 2025, and was attended by 27 participants. As a result, most of the participants showed a fairly good understanding of personal budget management.